2021
DOI: 10.1016/j.heliyon.2021.e08171
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of COX-2 and NADPH oxidase-4 by alpha-lipoic acid ameliorates busulfan-induced pulmonary injury in rats

Abstract: This study aimed to explore the potential protective effect of α-lipoic acid on busulfan-induced pulmonary fibrosis in rats.Main methods: Eighteen adult male rats were divided into 3 groups; control, busulfan, and busulfan plus α-lipoic acid groups. Lung index ratio, serum level of proinflammatory cytokine were assessed. The activities of antioxidant enzymes and lipid peroxidation products were estimated in the lung tissues in addition to the histopathological analyses. The deposition of the collagen in the lu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 51 publications
3
14
0
Order By: Relevance
“…The immunoperoxidase method was performed on three μm thick renal cortical transverse sections [ 44 , 45 , 46 ]. In brief, the slides were deparaffinized and endogenous peroxidase was blocked.…”
Section: Methodsmentioning
confidence: 99%
“…The immunoperoxidase method was performed on three μm thick renal cortical transverse sections [ 44 , 45 , 46 ]. In brief, the slides were deparaffinized and endogenous peroxidase was blocked.…”
Section: Methodsmentioning
confidence: 99%
“…Real-time PCR equipment (Pikoreal 96, ThermoScientific) was used to replicate cDNA templates. The amplification process consisted of a 20 μL total volume mixture [ 10 ] μL of HERA SYBR green PCR Master Mix (Willowfort, West Midlands, UK), 2 μL of cDNA template, 2 μL (10 pmol/μL) of each gene primer, and 6 μL of nuclease-free water], and was carried out using the following program: 95 °C for 2 min, followed by 40 cycles of 95 °C for 10 s, and 60 °C for 30 s. Glyceraldehyde-3-phosphate dehydrogenase (GAPDH) was employed as a control gene [ 25 ], and the sequences of the used primer pairs are listed in Table 2 . Vivantis provided the primer sets (Vivantis Technologies, Malaysia).…”
Section: Methodsmentioning
confidence: 99%
“…For instance, LA (20 mg/kg/day i.p. for 6 weeks) significantly decreased the levels of inflammatory cytokines (IL-1β, IL-6, IL-10 and TNF-α), a myofibroblast marker (α-SMA) and caspase-3 in the lungs of rats that were administered busulfan [119] . Previous studies suggested that COX-2-derived prostaglandins could reduce some histological changes in collagen production in models of lung fibrosis [120] , [121] .…”
Section: Lipoic Acid and Respiratory Diseasesmentioning
confidence: 96%
“…It has been recently shown that NOX-4 is expressed in pulmonary arterial adventitial fibroblasts and subsequently stimulates proliferation and inhibits apoptosis in fibroblasts [122] . Elhadidy et al reported that LA (20 mg/kg BW) decreased the deposition of collagen in busulfan-induced pulmonary fibrosis, which was associated with the upregulation of COX-2 and its downstream effector PGE2, as well as the downregulation of NOX-4 [119] . In another study, LA (50 mg/kg/day fora 28 days) regulated mitochondrial homeostasis and enhanced antioxidant activity to attenuate SiO 2 -induced pulmonary fibrosis by activating the AMPK/PGC1α and NRF2 pathways.…”
Section: Lipoic Acid and Respiratory Diseasesmentioning
confidence: 99%
See 1 more Smart Citation